Perjuangan Demi Hidup Yang Lebih Baik Seperti Tercermin Dalam Cerpen “Gadis Berkulit Hitam” Karya Sembene Ousmane - muhammad arief budiman (Universitas Aki, 2014)
Teaching literature in the class does not mean only teaching the theories, but also teaching about life to the students. The students need to absorb what is the behind of the theories which we teach. We also need to explain the function of the theories which we teach. The material is not only in use in class, but the material can also be functioned out side the class, in the real world. We can insert aspects of life in our teaching. One of the aspects that we can insert is character building. We should shape our students so that they have a good character. It is expected that our outputs are the students who have magnificent personality. The students should have a positive view of life. This character building can be done by both explicit and implicit ways. In explicit way we can use direct method which explains in detail many positive characters which should be acquired by all people. In implicit ways we can use literature teaching. There are many kinds of work of art, one of which is short story. Short story is free form of fiction which tells a slice of life of certain people. When we teach the theory of short story, we can also give an example of a short story. We should choose a short story which has a main character who has an outstanding personality. Here the writer chooses short story “Gadis Berkulit Hitam” of which the main character is hard worker and never gives up. Key Words : aspect of life, character building, literature teaching, short story